Wideband frequency reconfigurable metamaterial antenna employing SRR and CSRR for WLAN application - Adamu Y. Iliyasu; Mohamad Rijal Bin Hamid; Mohamad Kamal A Rahim; Mohd Fairus Bin Mohd Yusoff (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents the design of Wideband Frequency Reconfigurable Metamaterial Antenna by Employing Split Ring Resonator (SRR) and Complementary Split Ring Resonator (CSRR) for Wireles Area Network (WLAN) Apllication. The design is based on reconfiguring wideband metamaterial antenna by applying frequency reconfiguration technique. This was achieved by employing SRR and CSRR for bandwidth enhacement and two PIN Diode switches at different position for reconfiguration. The antenna has electrical dimention of    at 2.4 GHz. Computer Simulation Technology (CST) Software was used to determine the effectiveness of the technique. This design has several advantages like wider bandwidth which cover 2.4 GHz and 5.2 GHz WLAN bands, with three different single bands. From the simulation results, it was found that, the antenna has a bandwidth which covered 2.4 to 5.6 GHz, single bands at 2.5 GHz, 3.0 GHz and 3.5 GHz, with realized peak gain of 2.24 dBi and 3.9 dBi at 2.4 GHz and 5.2 GHz respectively and average efficiency of 96%. The antenna can be used for wireless application and cognitive radio application.